Plasma volume in normal and sickle cell pregnancy - Afolabi, Bosede (2011)
Plasma volume (PV) rises by up to 50% in normal pregnancy, a phenomenon associated with a favourable pregnancy outcome. A previous study of pregnant women with sickle cell (haemoglobin SS) disorder found that PV paradoxically contracts in late pregnancy.